AEROMAGNETIC STUDY OF THE CHURCHILL–SUPERIOR BOUNDARY IN NORTHERN MANITOBA - Kornik, L. J.; MacLaren, A. S. (Canadian Journal of Earth Sciences, 1966)
A regional aeromagnetic study of northern Manitoba suggests adjustments in the position of the Churchill–Superior boundary. This proposed boundary is correlated to a narrow, continuous magnetic low that changes direction at its northern end, from a northeast trend to an east–west trend that approximately parallels the 56° N. latitude line.The date pattern of age determinations chiefly supports the position of the proposed boundary. Comparison of aeromagnetic patterns to the geology establishes their close correlation. Aeromagnetic anomalies appear to be chiefly produced by near-surface material and can be correlated with the surface geology. A comparison of the gravity patterns to the aeromagnetic and geologic patterns establishes the apparent independence of the gravity patterns to the other two. The gravity anomalies appear to be produced by larger scale density contrasts which are not correlative with near-surface material. A deeper, crustal source of the gravity anomalies fits the evidence better.